Conceptual design of an 88-MHz KBSI radio-frequency quadrupole linear accelerator - Ok, Jung-Woo; Choi, Seyon; Yoon, Jang-Hee; Lee, Byoung-Seob; Park, Jin Yong; Won, Mi-Sook; Ahn, Jung Keun (Journal of the Korean Physical Society, 2013)
In order to accelerate ions, a radio-frequency quadrupole (RFQ) linear accelerator is being developed at the Korea Basic Science Institute (KBSI). The KBSI RFQ is designed to accelerate 1-pmA of lithium trivalent ions (A/Q = 7/3) by using a four-vane structure. We chose 88-MHz for the RF operating frequency. The energy of the beam injected into the RFQ is 12 keV/u whereas the energy of the downstream output beam is 300 keV/u. The beam dynamics inside RFQ linear accelerator was studied using the PARMTEQM code. The length of the RFQ was approximately 2 m with a transmission rate of 97.4% for lithium trivalent ions. For the structural design, a 2-dimensional geometry structure was studied using the SUPERFISH code near the resonance frequency of the quadrupole and the dipole modes. The 3-dimensional field distributions inside the RFQ cavity were investigated using CST Microwave Studio. The RFQ’s conceptual design and preliminary results for this model are reported.